Evaluative Analysis on MOOC with LMS Based to Improve English Teachers’ Teaching Competences - Hidayah, Siti Nurul (IJET (Indonesian Journal of English Teaching), 2022)
In the 5th Industrial Revolution era, English teaching method blended with technology and information-based skills will be more noteworthy to improve English teachers’ teaching aptitudes. Here, the role of Non-Formal Training Institute (LKP) with its new teaching framework is very crucial to increase English teachers’ teaching competences in this industrial revolution era, improve their students’ attainment and advance their professional knowledge. To optimize this role, this research was conducted using Kirkpatrick's 4-level evaluation model, to assess the implementation of Massive Open Online Course (MOOC) with Learning Management System (LMS) based in non-formal educational context for many English teachers in Indonesia. This study aimed to determine the benefits and constraints of implementing this online course using evaluative techniques with quantitative and qualitative research methodologies. Data collection techniques were interviews, document observation and questionnaires. The results showed that at the reaction level, the research participants gave a positive response to the online course, the participants also succeeded in increasing their teaching knowledge (learning level), changing behavior in teaching English (behavior level), and improving their students’ achievement (level result). The greatest benefits felt by participants included beneficial topics, video materials, and video conferencing frames which had a direct impact on their teaching knowledge and skills development. The obstacles faced by the participants were problems with internet access, video conference access, and assignments.